Fazer-se comunitário em Maraã (AM): uma etnografia da experiência de comunidades ribeirinhas a partir da figura do professor comunitário - Matheus Machado Vaz (2019)
In the Middle Solimoes, since the 1960s, the community organization invented a new model of demand management, characterized by self-management and specific forms of social relations. A new kind of social configuration emerges, giving rise to specific aspects in the formation of the comunitário. In this project of raising children together, the school and the teacher have a fundamental role in the constitution of the new comunitário, theme of this ethnography of the experience of riverside communities in Maraã in the conduction of their schools through the axes of territoriality, sociality and constitution of the person.